Case report: Novel p.Val306Met missense mutation in TRPV3 in a case of Olmsted syndrome accompanied by squamous cell carcinoma - Hao, Yangyang; Wu, Rong; Chen, Xi; Shen, Yunjia; Chou, Mengwei; Yang, Jianqiang (Frontiers in Oncology, 2024)
Olmsted syndrome (OS) is a rare congenital skin disorder, typically characterized by symmetrical, severe palmoplantar and periorificial keratoderma, often accompanied by alopecia, and onychodystrophy, with varying degrees of pruritus and pain. Gain-of-function variants of the transient receptor potential cation channel subfamily V member 3 (TRPV3) were described as a cause of OS. Here, we report an atypical case of OS caused by a novel mutation in the TRPV3 gene that has not been described before in OS. The patient presented with disabling, bilateral palmoplantar keratoderma, and subsequently developed squamous cell carcinoma on the right sole. Genetic analysis identified a novel heterozygous p.Val306Met missense mutation in the exon 8 of TRPV3. Our findings expand the phenotypic spectrum of TRPV3-related OS and underscore the need for vigilant long-term monitoring of these patients.